Real time FPGA implementation of induction machine model - A novel approach - Duman, Erkan; Can, Hayrettin; Akin, Erhan (Ieee, 2007)
This paper presents the real-time hardware implementation of three-phase induction motor modelling, using a Field Programmable Gate Array (FPGA) device, in order to use in real-time simulations. The proposed model runs directly in hardware by using FPGA technology and it allows a remarkable speed up in comparison with conventional models which based only software. Such a model was developed with the aim of meeting the real-time simulations needs while solving the limitations of traditional solutions, in particular for hardware-in-the-loop simulation of electrical machines and systems. In the previous studies, this technology had been only used to implement I/O processes of simulations due to insufficient devices having the constraints about the size and the number of the general purposed ports. However in more recent times, higher densities, higher speed and cost advantages have enabled the use of such devices in a wider variety of applications. In this paper, we defined the three-phase induction motor by state-space representation which models a system as a set of differential equations using matrix form. Therefore our system was transformed into an application of real-time matrix multiplication in FPGA using floating point number system. We utilized Quartus-II environment to develop FPGA designs and then download these design files into our development kit.
Joint Conference on Electromotion/IEEE Aegean Conference on Electrical Machines and Power Electronics/ -- SEP 10-12, 2007 -- Bodrum, TURKEY